A novel structural polyimide material with synergistic phosphorus and POSS for atomic oxygen resistance. Issue 16 (21st January 2015) - Song, Guanghe; Li, Xuesong; Jiang, Qiyang; Mu, Jianxin; Jiang, Zhenhua
Abstract : A series of phosphorus-containing polyimide–POSS nanocomposites were synthesized, phosphorus and POSS synthetic self-passivating layers were formed to protect the underlying material from AO attack. Abstract : A series of novel structural phosphorus-containing polyimide–polyhedral oligomeric silsesquioxane (POSS) nanocomposites with varying phosphorus contents were synthesized. The nanocomposites displayed outstanding thermal properties. The glass transition temperature was increased to 294.87 °C when the phosphorus content was 1.61 wt% and the anti-degradation properties were also obviously enhanced. Moreover, the nanocomposites presented much higher atomic oxygen (AO) durability compared with pure polyimide because of the incorporation of special functional groups of phosphorus oxide and POSS. The AO erosion yields decreased to 51.9% of pure polyimide–POSS nanocomposites when the phosphorus content was increased to 1.61 wt%. Furthermore, the mechanism of phosphorus and POSS synergistic AO resistance was explored via XPS and SEM. Three kinds of silicon particles with different binding energies and two kinds of phosphorus elements with different binding energies were formed because of AO exposure and the phosphorus and POSS synergy. Highly effective self-passivating layers were formed to protect the underlying material from AO attack.